Amputation for Complex Regional Pain Syndrome: Meta-Analysis and Validation of a Histopathology Scoring System. Issue 4 (10th November 2022) - Howard, Emily L; Singleton, Michael; Soulakvelidze, Irakli
Abstract: Objective: Pathology can provide crucial insights into the etiology of disease. The goal of this review is to evaluate the rigor of histopathology reports of Complex Regional Pain Syndrome (CRPS). Methods: A systematic search of multiple databases identified papers that described amputation for CRPS with pathology findings. Control pathology articles were randomly chosen from the same journals. Landmark articles in Surgical Pathology were previously identified. Papers were categorized by the use of histology: Anatomic (microscopic description), Diagnostic (binary result), and Substrate (special studies only). A novel Histopathology Score assigned 1 point for each of 10 History elements and 15 Pathology elements. All articles were scored and analyzed by appropriate statistics. Results: The search identified 22 CRPS, 50 Control and 50 Landmark articles. Multivariable analysis of the Pathology Score showed a significantly higher score for Anatomic vs Non-Anatomic papers (Incidence Rate Ratio (IRR) 1.54, P  < .001) and Landmark vs CRPS articles (IRR 1.39, P value .003). CRPS papers reported some elements infrequently: diagnostic criteria (31.8%), routine stain (50%), any clinic-pathologic correlation (40.9%), and sample size >2 (27.3%). Conclusions: The Pathology Score is a useful quality assessment tool to evaluate studies. As expected, Anatomic papers scored significantly higher than Non-Anatomic papers. CRPS papers had small sample sizes (median 1) and infrequent reporting of diagnostic criteria, routine stain, any clinical pathologic correlation. These particular elements are crucial for analyzing and reviewing pathologic features. The analysis explains why it is quite difficult to write a meaningful systematic review of CRPS histology at this time.